2020
DOI: 10.1016/j.jmb.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Hsp90 N Domain Identify a Site that Controls Dimer Opening and Expand Human Hsp90α Function in Yeast

Abstract: Hsp90 is a highly conserved molecular chaperone important for the activity of many client proteins. Hsp90 has an N-terminal ATPase domain (N), a middle domain (M) that interacts with clients and a C-terminal dimerization domain (C). “Closing” of dimers around clients is regulated by ATP binding, co-chaperones, and post-translational modifications. ATP hydrolysis coincides with release of mature client and resetting the reaction cycle. Humans have two Hsp90s: hHsp90α and hHsp90β. Although 85% identical, hHsp90β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…1A ). As previously observed, hHsp90α did not complement as well as hHsp90β, as seen by much weaker growth on FOA 33 35 . While CnHsp90 and EhHsp90 complemented S. cerevisiae Hsp90 function well, PfHsp90 complemented less well, similarly to hHsp90α.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…1A ). As previously observed, hHsp90α did not complement as well as hHsp90β, as seen by much weaker growth on FOA 33 35 . While CnHsp90 and EhHsp90 complemented S. cerevisiae Hsp90 function well, PfHsp90 complemented less well, similarly to hHsp90α.…”
Section: Resultssupporting
confidence: 82%
“…To understand how Hsp90-EA supported growth, we used fluorescence-based techniques to investigate whether EA altered nucleotide-mediated conformational rearrangements in Hsp82, which are essential to its function in vivo. Rearrangements associated with formation of the closed-clamp such as N-M domain docking, lid repositioning and β-strand swapping are observed via photoinduced electron transfer (PET) 7 , 28 , 33 . A cysteine and a tryptophan residue are introduced at defined positions depending on which movement is to be measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was proposed that the lid acts as a nucleotide-sensitive conformational switch of the molecular chaperone activity 36 . There would be a strong correlation between the chaperone activity and the ATP vs. ADP binding 30 , 37 , 38 . In contrast, it was also reported that the transitions between the conformational states and the nucleotide binding/unbinding are mainly thermally driven, with large conformational fluctuations on timescales faster than the rate of ATP hydrolysis 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%